2016
DOI: 10.1136/bmjspcare-2014-000811
|View full text |Cite
|
Sign up to set email alerts
|

The death of patients with terminal cancer: the distress experienced by their children and medical professionals who provide the children with support care

Abstract: An important finding of the study is that the participants' grief reaction to their parents' deaths during childhood was prolonged. Moreover, hospital medical professionals may find it difficult to directly support affected children. Comprehensive support involving organisations (eg, local communities) may be necessary for children who have lost a parent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…, Delihn & Reg , Otani et al . ) and expert opinion. The items focused on the behaviour of adolescents who had experienced the cancer or death of a parent/grandparent.…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations
“…, Delihn & Reg , Otani et al . ) and expert opinion. The items focused on the behaviour of adolescents who had experienced the cancer or death of a parent/grandparent.…”
Section: The Studymentioning
confidence: 99%
“…There are no scales measuring normal grief reactions in adolescents available in Japan. Therefore, we developed grief reaction items for this study based on previous qualitative research (Berman et al 1988, Christ 2000, Beale et al 2004, Delihn & Reg 2009, Otani et al 2016) and expert opinion. The items focused on the behaviour of adolescents who had experienced the cancer or death of a parent/grandparent.…”
Section: Grief Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,11 These children are known to harbor fears about their parent getting worse 7,12,13 or dying from the disease, leaving the child alone or raised by someone else. 7,12,14 These fears likely crescendo in the days before a parent dies, as a child anticipates the coming loss. 9,[15][16][17] Moreover, several studies of cancer-bereaved youth have shown significant long-term consequences on the child, including twice the risk of self-injury compared with nonbereaved peers and higher levels of post-traumatic stress symptoms compared with pediatric cancer survivors.…”
Section: Introductionmentioning
confidence: 99%